2021
DOI: 10.1016/j.envpol.2021.116908
|View full text |Cite
|
Sign up to set email alerts
|

The fate of plastic litter within estuarine compartments: An overview of current knowledge for the transboundary issue to guide future assessments

Abstract: Plastics can enter biogeochemical cycles and thus be found in most ecosystems. Most studies emphasize plastic pollution in oceanic ecosystems even though rivers and estuaries are acknowledged as the main sources of plastics to the oceans. This review detected few studies approaching the transboundary issue, as well as patterns of estuarine gradients in predicting plastic distribution and accumulation in water, sediments, and organisms. Quantities of plastics in estuaries reach up to 45,500 items m À3 in water,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 171 publications
(248 reference statements)
0
8
0
Order By: Relevance
“…The wide availability of MPs is expected to threaten biodiversity throughout the marine environment. Plastic debris is found all along the coastal zone, continental slope, around oceanic islands, seamounts, and even in the deepest parts of the ocean (Cai et al, 2018;Monteiro et al, 2018;Lins-Silva et al, 2021;Pinheiro et al, 2021). Differences in the ecological habits, such as feeding strategy and migration, might influence the MP uptake by marine species.…”
Section: Discussionmentioning
confidence: 99%
“…The wide availability of MPs is expected to threaten biodiversity throughout the marine environment. Plastic debris is found all along the coastal zone, continental slope, around oceanic islands, seamounts, and even in the deepest parts of the ocean (Cai et al, 2018;Monteiro et al, 2018;Lins-Silva et al, 2021;Pinheiro et al, 2021). Differences in the ecological habits, such as feeding strategy and migration, might influence the MP uptake by marine species.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to coral reefs, saltmarshes also have a significant potential in wave height reduction and shoreline protection. In fact, salt marshes and mangroves provide a high number of benefits (erosion control, coastal protection, tourism and recreation, food and raw materials, nursery habitat for fish, pollution storage, water purification and carbon sequestration and education) (Barbier et al 2011;Celis Hernandez et al 2020a, b;Pinheiro et al 2021). Saltmarshes are located at high elevation intertidal zones and hence can be more effective in wave attenuation compared to seagrass meadows or coral reefs, which are found in lower intertidal/subtidal areas (Bouma et al 2014).…”
Section: Advantages and Limitations Of Using Bioshield For Coastal Pr...mentioning
confidence: 99%
“…Polymer detection in this study showed common polymer types that are commercially produced and highly consumed, including PE, polypropylene, polystyrene, and polyvinyl chloride (Wang et al, 2021;Yuan et al, 2022). They are commonly found in the environment because of their frequent disposal (short service life) and light weight, meaning they can easily be carried in the environment (Pinheiro et al, 2021). All of the above polymers were categorized by Brown (2022) as hazardous agents produced from plastic processing.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 91%